Housing Development for Low-Income Communities (Mbr) in Indonesia - Risna Sari, Ade (Decision, 2023)
Policy Network in Housing Development for Low-Income Communities (MBR) in Indonesia. This study is driven by the author's interest in policies that involve a variety of multi-sector actors, including the government, private housing developers, academics, the community, and the media. This study uses Frans Van Waarden's (1992) theory of policy network dimensions, which comprises players, functions, structures, institutionalization, rules of action, power relations, and actor tactics. The method utilized is descriptive with a qualitative focus. Data were gathered through a literature review and a field investigation (observations and interviews). The technique for determining informants is purposive sampling. The findings of this study show that the policy network in housing development for MBR in Indonesia does not yet meet the dimensions of a policy network, including the role of the community itself, which is not directly involved and tends to be less active because the community's aspirations and complaints are currently communicated only through NonGovernmental Organizations. (NGOs), there is no functioning mechanism integrated into the policy network, there is no regular schedule of meetings held amongst actors, therefore coordination is carried out more frequently via WhatsApp Group exclusively, and policy actors are not making the best use of existing information channels.